Treatment of glabella skin necrosis following injection of hyaluronic acid filler using platelet-rich plasma. (17th February 2016) - Kang, Boo Kyoung; Kang, In Jung; Jeong, Ki Heon; Shin, Min Kyung
Abstract : Hyaluronic acid (HA) fillers have been widely used for soft-tissue augmentation. However, there can be various complications following HA filler injection. Skin necrosis is rare but one of the most disastrous side effects that, if not treated promptly and effectively, can result in permanent and potentially disfiguring scarring. Thus, early proper management is important. Herein we report a patient who experienced tissue necrosis of the glabellar area after receiving filler injections that was successfully treated using platelet-rich plasma and provide full follow-up clinical photographs.